Composite slag-based concrete admixture and preparation method thereof

By chemically modifying the phosphorus slag and iron slag, and combining them with fly ash, kaolin, modified composite fiber and other materials, composite slag-based concrete admixtures are prepared, and the existing high-performance concrete admixtures are solved. The problems of high price and poor liquidity have achieved improvements in concrete performance and high-value utilization of industrial solid waste.

CN119461933AInactive Publication Date: 2025-02-18湖北津耀德新材料科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411711437.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing mineral blends of high-performance concrete have problems such as expensive and poor liquidity, and have failed to effectively utilize industrial solid waste, which affects the resistance to carbonization and salt corrosion.

Method used

Using phosphorus slag and iron slag as raw materials, chemically modified treatment, combined with fly ash, kaolin, modified composite fiber and other materials, to prepare composite slag-based concrete blends, optimize the internal structure of concrete, improve mechanical properties and resistance Scratch ability.

Benefits of technology

The high-value recycling and utilization of phosphorus slag and iron slag has been achieved, the mechanical properties, crack resistance and salt corrosion resistance of concrete have been improved, and the production cost has been reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005155829930000161
    Figure BDA0005155829930000161
Patent Text Reader

Abstract

The invention discloses a composite slag-based concrete admixture and a preparation method thereof, the composite slag-based concrete admixture comprises the following raw materials by weight: 50-70 parts of modified composite slag, 15-25 parts of fly ash, 10-15 parts of kaolin, 10-15 parts of an additive, and 15-25 parts of modified composite fiber; wherein the admixture is formed by mixing glass beads, latex powder, coal gangue and aluminum sulfate according to the mass ratio of (15-25): (10-15): (8-12): (5-9). According to the admixture, phosphorus slag and iron-ore slag are used as raw materials, the surface is modified through a chemical method, meanwhile, fly ash, kaolin, coal gangue, latex powder, glass beads, aluminum sulfate and modified composite fibers are used as auxiliary materials, high-value recycling of the phosphorus slag and the iron-ore slag is achieved, and the internal structure of concrete is optimized; the mechanical property, the crack resistance and the salt corrosion resistance of the concrete are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete, and particularly relates to a composite slag-based concrete admixture and a preparation method thereof. Background Art

[0002] Admixtures are inorganic mineral powders that replace part of the cement when preparing concrete and improve the performance of concrete. With the rapid development of my country's construction industry, there are higher requirements for the working performance, strength grade, and durability of concrete, and the demand for high-performance concrete is increasing. High-performance concrete is widely used in the construction industry for its excellent mechanical properties and durability. However, the preparation of high-performance concrete has higher requirements on the performance of various raw materials. At present, the mineral admixtures widely used in high-performance concrete mainly include ground slag powder, silica powder, and kaolin, but they have disadvantages such as high price and are not conducive to the fluidity of concrete, and have certain limitations in application.

[0003] With the rapid development of my country's economy and the rapid development of infrastructure, the generation of industrial solid waste is also accelerating. However, the resulting storage of industrial solid waste damages the soil and pollutes the environment. How to comprehensively utilize industrial solid waste, reduce emissions, and utilize it as resources has become a focus of social attention.

[0004] Phosphate slag is a common slag component produced in industrial production, especially the main waste slag component produced in the production of yellow phosphorus by electric furnace method. The amount of phosphate slag produced in the process of extracting yellow phosphorus is often 8-10 times that of the extracted yellow phosphorus. Research on industrial waste slag has been conducted all over the world. In the long-term research process, people have gradually discovered that phosphate slag is of great help in improving the performance of concrete. For example, phosphate slag is rich in a variety of chemical components, among which the three more prominent active chemical components can react with cement in the concrete production process, thereby improving the comprehensive performance of concrete.

[0005] Chinese patent CN113233830A discloses a method for producing composite mineral admixtures from ferromanganese slag, comprising the following steps: step 1: obtaining ferromanganese slag, industrial waste slag, gypsum, admixture, and cement, crushing and grinding the obtained ferromanganese slag and industrial waste slag to obtain ferromanganese slag powder and steel slag powder, wherein the ferromanganese slag powder accounts for 8-20% of the raw materials, the steel slag powder accounts for 2-6% of the raw materials, the gypsum powder accounts for 12-6% of the raw materials, the admixture accounts for 2-6% of the raw materials, and the cement accounts for 60-85% of the raw materials; the method is not only simple and convenient to manufacture, but also can make good use of the ferromanganese slag to prepare it into one of the raw materials for concrete, not only reduces the space occupied by the ferromanganese slag, but also reduces the cost of concrete; the slag bricks made of the ferromanganese slag have a smooth and dense surface and a strength of 19.6MPa, are more practical, and are very simple to operate; at the same time, the manufacturing environment and requirements are relatively low, and can be promoted and applied on a large scale. Chinese patent CN110240434A discloses a titanium slag powder-phosphorus slag powder composite admixture and its preparation method and application method, which belongs to the field of building materials technology, and aims to provide a composite admixture that improves the early strength of concrete and reaches the tensile strength of C50 prestressed concrete continuous beams more quickly; reduces the viscosity of concrete mixtures and improves the workability of concrete mixtures. The main points of its technical solution are as follows: calculated by mass fraction, it includes the following components: 10-30 parts of slag powder, 10-30 parts of titanium-containing slag powder, 20-40 parts of phosphorus slag powder, 15-40 parts of silica fume, and 1-5 parts of activator; slag powder is water-quenched blast furnace slag powder; phosphorus slag powder is granulated electric furnace phosphorus slag powder. This invention is suitable for the batching of C50 beam concrete and has industrial value. However, none of the above patents process the slag powder. It is only added to the concrete in the form of raw material doping, which may affect the concrete's anti-carbonation and salt erosion resistance in the later stage. Summary of the invention

[0006] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a composite slag-based concrete admixture and a preparation method thereof. The admixture uses phosphate slag and iron slag as raw materials, and the surface is modified by chemical methods. At the same time, it is supplemented with fly ash, kaolin, coal gangue, latex powder, glass beads, aluminum sulfate and modified composite fibers, thereby achieving high-value recycling of phosphate slag and iron slag, and optimizing the internal structure of concrete, thereby improving the mechanical properties, crack resistance and salt erosion resistance of concrete.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] A composite slag-based concrete admixture, comprising the following raw materials in parts by weight:

[0009] 50-70 parts of modified composite slag, 15-25 parts of fly ash, 10-15 parts of kaolin, 10-15 parts of admixture, 15-25 parts of modified composite fiber;

[0010] The admixture is a mixture of glass microspheres, latex powder, coal gangue and aluminum sulfate in a mass ratio of 15-25:10-15:8-12:5-9.

[0011] Preferably, a composite slag-based concrete admixture comprises the following raw materials in parts by weight:

[0012] 50-60 parts of modified composite slag, 20-25 parts of fly ash, 10-15 parts of kaolin, 10-15 parts of admixture, and 20-25 parts of modified composite fiber.

[0013] More preferably, a composite slag-based concrete admixture comprises the following raw materials in parts by weight:

[0014] 55-60 parts of modified composite slag, 20-23 parts of fly ash, 12-15 parts of kaolin, 13-15 parts of admixture, and 20-22 parts of modified composite fiber.

[0015] In the present invention, fly ash has a high specific surface area, and the active SiO2 therein has an extremely high volcanic ash effect, which can react with Ca(OH)2 crystals to generate CSH gel material, thereby reducing the porosity of the modified composite slag-cement paste interface layer, making the concrete structure denser and improving the interface adhesion.

[0016] Preferably, the method for preparing the modified composite slag comprises the following steps:

[0017] S1, adding phosphate slag and iron slag into sodium hydroxide solution for impregnation treatment, filtering and drying after the treatment to obtain composite slag;

[0018] S2, adding the composite slag in step S1 to an ethanol aqueous solution, then adding vinyltrimethoxysilane, stirring, filtering, washing, and drying after the treatment to obtain a composite slag containing double bonds;

[0019] S3, adding the double bond-containing composite slag in step S2 into xylene, and then adding allyl dimethyldithiocarbamate, acrylic acid, and dibenzoyl peroxide to carry out a constant temperature reaction, and after the reaction is completed, adding a solution to adjust the pH to 7, followed by filtering, washing, and drying to obtain a modified composite slag.

[0020] Preferably, in step S1, the mass ratio of the phosphate slag to the iron slag is 10:5-10, the concentration of the sodium hydroxide is 40-80 g / L, the temperature of the immersion treatment is 45-55° C., and the time is 2-3 h.

[0021] More preferably, in step S1, the mass ratio of the phosphate slag to the iron slag is 10:7-10, the concentration of the sodium hydroxide is 60-80 g / L, the temperature of the immersion treatment is 50-55° C., and the time is 2-2.5 h.

[0022] Preferably, the volume concentration of ethanol in the ethanol aqueous solution in step S2 is 70-80%, the mass ratio of the composite slag to vinyltrimethoxysilane is 100:15-20, the temperature of the stirring treatment is 60-70°C, and the time is 3-5h.

[0023] More preferably, the volume concentration of ethanol in the ethanol aqueous solution in step S2 is 75-80%, the mass ratio of the composite slag to vinyltrimethoxysilane is 100:15-18, the temperature of the stirring treatment is 65-70° C., and the time is 3-4 h.

[0024] In the present invention, the phosphorus slag particles contain a small amount of phosphorus. Since the bond energy of the phosphorus oxygen bond and the silicon oxygen bond is large, that is, the ion bonding is strong, the chemical bond is not easy to break in the early stage of cement hydration and cannot quickly participate in the volcanic ash reaction, and the breaking process of the chemical bond is accelerated by a strong alkaline substance. The iron content in the iron slag is relatively high, and it has a certain activity. It can react chemically with the hydration product, promote the hydration and hardening process of the concrete, and improve the crack resistance, impermeability and durability of the concrete. By compounding and modifying the two, as the main raw material of concrete admixtures, the performance of the concrete can be effectively improved, the production cost can be reduced, and the comprehensive utilization of resources and environmental protection can be promoted.

[0025] Preferably, in step S3, the mass ratio of the pretreated composite slag, xylene, allyl dimethyldithiocarbamate, acrylic acid, and dibenzoyl peroxide is 100:800-1200:20-30:10-15:1-2, and the isothermal reaction temperature is 70-80° C. and the reaction time is 3-4 h.

[0026] More preferably, in step S3, the mass ratio of the pretreated composite slag, xylene, allyl dimethyldithiocarbamate, acrylic acid, and dibenzoyl peroxide is 100:1000-1200:25-30:10-13:1-1.5, and the isothermal reaction temperature is 75-80° C. and the reaction time is 3-3.5 h.

[0027] In the present invention, allyl dimethyl dithiocarbamate and acrylic acid are introduced into the composite slag, which is conducive to the uniform dispersion of the composite slag in the concrete system. At the same time, the introduced dithioamino groups have a great influence on the Ca 2+ It has good adsorption capacity, accelerates the hydration reaction of concrete, and thus improves the early strength of concrete.

[0028] Preferably, the method for preparing the modified composite fiber comprises the following steps:

[0029] (a) adding basalt fiber and polyester fiber into a low-temperature plasma apparatus for plasma treatment, and obtaining pretreated composite fiber after the treatment;

[0030] (b) adding the pretreated composite fiber in step (a) into dimethylformamide, and then adding 7-amino-1,3-naphthalene disulfonic acid, glutaraldehyde, and triethylamine, heating to react under a nitrogen atmosphere, and filtering, washing, and drying after the reaction is completed to obtain the modified composite fiber.

[0031] Preferably, the mass ratio of the basalt fiber to the polyester fiber in step (a) is 1:1-2, and the plasma treatment process is: under a nitrogen atmosphere, the vacuum degree in the vacuum chamber of the plasma instrument is 20-30Pa, the treatment time is 1-3min, and the treatment power is 100-130W.

[0032] More preferably, the mass ratio of the basalt fiber to the polyester fiber in step (a) is 1:1-1.5, and the plasma treatment process is: under a nitrogen atmosphere, the vacuum degree in the vacuum chamber of the plasma instrument is 25-30 Pa, the treatment time is 1-2 min, and the treatment power is 110-130 W.

[0033] In the present invention, polyester fiber is not only beneficial to improve crack resistance, but also has good chemical stability and relatively low cost. However, the chemically inert surface of polyester fiber has poor bonding with the cement matrix, and its surface needs to be modified. Basalt fiber is an inorganic continuous layered fiber spun from natural basalt by high-temperature melting and drawing. It has the characteristics of high strength, high elastic modulus, high temperature resistance, corrosion resistance, and small thermal expansion coefficient. It is an ideal cement reinforcing fiber. However, due to the smooth surface of basalt fiber, fewer active functional groups, and chemical inertness, its application is limited to a certain extent. The two fibers are surface treated by a plasma instrument to improve their surface activity and roughness, which is conducive to the subsequent reaction.

[0034] Preferably, in step (b), the mass ratio of the pretreated composite fiber, 7-amino-1,3-naphthalene disulfonic acid, glutaraldehyde and triethylamine is 100:30-40:10-20:40-50; the temperature of the heating reaction is 75-85°C and the time is 4-7h.

[0035] More preferably, in step (b), the mass ratio of the pretreated composite fiber, 7-amino-1,3-naphthalene disulfonic acid, glutaraldehyde and triethylamine is 100:35-40:15-20:45-50; the temperature of the heating reaction is 80-85° C., and the time is 4-6 hours.

[0036] In the present invention, glutaraldehyde is used as a cross-linking agent to introduce 7-amino-1,3-naphthalene disulfonic acid into the surface of the composite fiber, so that the surface of the modified composite fiber contains a large number of sulfonic acid groups and naphthyl groups, which not only improves the hydrophilicity and adhesion of the composite fiber, but also improves the dispersibility of the composite fiber in concrete and improves the density of the composite fiber-matrix interface. At the same time, the naphthyl groups are hydrogen-bonded with the surface of cement particles to form a chemical adsorption layer, which reduces the adsorption force between cement particles, reduces the viscosity of concrete, improves plasticity, and improves the processing performance of concrete.

[0037] The present invention also protects a method for preparing the composite slag-based concrete admixture as described above, comprising the following steps:

[0038] The modified composite slag, fly ash, kaolin, admixture and modified composite fiber are weighed in parts by weight, and stirred at 500-800 r / min for 20-30 min to obtain the composite slag-based concrete admixture.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] (1) The composite slag concrete admixture provided by the present invention is prepared by subjecting phosphorus slag and iron slag to modification treatment. First, the composite slag is subjected to alkali treatment to etch the surface of the slag to improve the surface roughness and reaction activity. Subsequently, the composite slag is reacted with vinyltrimethoxysilane to introduce double bond groups onto the slag surface through the action of silicon-oxygen bonds. Then, the composite slag containing double bonds is reacted with allyl dimethyldithiocarbamate and acrylic acid to graft allyl dimethyldithiocarbamate and acrylic acid onto the slag surface. The sulfur atoms in the dithioamino groups can coordinate with the calcium ions in the slurry to preferentially nucleate Ca(OH)2 at the interface between the slag and cement, thereby accelerating the hydration reaction of the cement matrix and improving the early strength of the concrete. At the same time, the dithioamino groups and carboxyl groups are introduced onto the slag surface through chemical bonds to improve the bonding strength between the slag and cement and improve the durability of the concrete.

[0041] (2) The modified composite fiber added to the composite slag concrete admixture provided by the present invention is composed of basalt fiber and polyester fiber in a specific ratio. The low elastic modulus fiber and the high elastic modulus fiber are mixed to achieve a multi-level synergistic effect, thereby better improving the interface performance of the fiber concrete, so that the modified fiber plays a role in different stages of reinforcing the concrete and complements each other. The polyester fiber can limit the occurrence and growth of cracks, prevent micro cracks from developing into macro cracks, and reduce the chemical erosion of the concrete. The basalt fiber has high rigidity and can improve the flexural resistance of the concrete material. The composite fiber not only plays the role of a single fiber but also produces a synergistic effect between the fibers, thereby improving the mechanical properties of the concrete. In addition, by surface modification of the composite fiber, the roughness of the fiber surface is increased, so that dense hydrates with a high degree of hydration are generated around the fiber, thereby improving the bonding performance of the composite fiber-concrete interface. At the same time, the introduction of sulfonic acid groups and naphthyl groups not only improves the hydrophilicity and bonding properties of the composite fiber, but also improves the dispersibility of the composite fiber in concrete, thereby improving the density of the composite fiber-matrix interface.

[0042] (3) The composite slag concrete admixture provided by the present invention uses modified composite slag and modified composite fiber as main raw materials, and is supplemented with fly ash, kaolin, coal gangue, latex powder, glass beads, and aluminum sulfate. When added to concrete, it can improve the working performance of concrete, optimize the internal structure of concrete, and improve the density, mechanical properties, crack resistance and salt erosion resistance of concrete, thereby realizing the high-value recycling of phosphate slag and iron slag. DETAILED DESCRIPTION

[0043] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] In the present invention, the phosphate slag is produced in Guiyang, Guizhou Province, with a density of 2.88 g / cm 3, chemical composition is shown in Table 1; the iron slag is the iron slag powder of Yunnan Desheng Iron and Steel Co., Ltd., and the chemical composition is shown in Table 1; the fly ash is purchased from Emeishan Taixin Environmental Protection Technology Co., Ltd., which is Class II fly ash with a particle size of 10-30μm; the kaolin is purchased from Hebei Qingjiang New Materials Technology Co., Ltd., with a mesh size of 1250 mesh; the glass microbeads are purchased from Hebei Sanliujiu New Materials Technology Co., Ltd., with a mesh size of 300 mesh; the latex powder is purchased from Hebei Hongzheng Technology Co., Ltd.; the coal gangue is purchased from Lingshou Zhuoye Mineral Products Processing Plant, with a mesh size of 325 mesh; the basalt fiber is purchased from Shandong Taicheng Fiber Co., Ltd., with a diameter of 17μm and a length of 6mm; the polyester fiber is purchased from Tai'an Songze Composite Materials Co., Ltd., with a diameter of 10-25μm and a length of 6mm.

[0045] Table 1 Chemical composition (mass fraction %)

[0046] raw material <![CDATA[SiO2]]> <![CDATA[Fe2O3]]> <![CDATA[Al2O3]]> CaO MgO <![CDATA[K2O]]> <![CDATA[SO3]]> <![CDATA[Na2O]]> <![CDATA[P2O5]]> loss Phosphate slag 37.21 0.23 3.37 44.92 3.64 0.62 0.07 0.26 2.48 -2.45 Iron ore slag 31.82 3.29 10.25 36.83 3.18 0.07 0.04 0.05 1.97 -0.21

[0047] Example 1

[0048] A method for preparing a composite slag-based concrete admixture comprises the following steps:

[0049] According to the formula, 6 kg of modified composite slag, 2 kg of fly ash, 1.3 kg of kaolin, 1.2 kg of admixture, and 2 kg of modified composite fiber were weighed and stirred at 700 r / min for 25 min to obtain the composite slag-based concrete admixture.

[0050] Wherein, the admixture is a mixture of glass microspheres, latex powder, coal gangue and aluminum sulfate in a mass ratio of 20:13:10:7;

[0051] The preparation method of the modified composite slag comprises the following steps:

[0052] S1, adding 1kg of phosphate slag and 0.8kg of iron slag into a sodium hydroxide solution with a concentration of 60g / L, immersing at 50°C for 2.5h, filtering and drying after the treatment to obtain composite slag;

[0053] S2, adding 1 kg of the composite slag in step S1 to 10 L of ethanol aqueous solution (the volume concentration of ethanol is 75%), then adding 180 g of vinyltrimethoxysilane, stirring at 65° C. for 4 h, filtering, washing and drying after the treatment to obtain a composite slag containing double bonds;

[0054] S3. Add 1 kg of the double bond-containing composite slag in step S2 into 10 L of xylene, then add 250 g of allyl dimethyldithiocarbamate, 130 g of acrylic acid, and 15 g of dibenzoyl peroxide, and react at 75 °C for 3.5 h. After the reaction is completed, add sodium hydroxide solution to adjust the pH to 7, then filter, wash, and dry to obtain modified composite slag.

[0055] The method for preparing the modified composite fiber comprises the following steps:

[0056] (a) 1 kg of basalt fiber and 1.5 kg of polyester fiber were added into a low-temperature plasma instrument, and plasma treatment was performed under a nitrogen atmosphere with a vacuum degree of 25 Pa and a power of 120 W for 2 min. After the treatment, pretreated composite fibers were obtained;

[0057] (b) Add 1 kg of the pretreated composite fiber in step (a) into 15 L of dimethylformamide, and then add 350 g of 7-amino-1,3-naphthalene disulfonic acid, 150 g of glutaraldehyde, and 450 g of triethylamine, and react in a nitrogen atmosphere at 80° C. for 6 hours. After the reaction is completed, filter, wash, and dry to obtain the modified composite fiber.

[0058] Example 2

[0059] A method for preparing a composite slag-based concrete admixture comprises the following steps:

[0060] According to the formula, 6.5 kg of modified composite slag, 2 kg of fly ash, 1.2 kg of kaolin, 1.3 kg of admixture, and 2 kg of modified composite fiber were weighed and stirred at 600 r / min for 25 minutes to obtain the composite slag-based concrete admixture.

[0061] Wherein, the admixture is a mixture of glass microspheres, latex powder, coal gangue and aluminum sulfate in a mass ratio of 20:12:10:8;

[0062] The preparation method of the modified composite slag comprises the following steps:

[0063] S1. Add 1 kg of phosphate slag and 0.7 kg of iron slag into a sodium hydroxide solution with a concentration of 70 g / L, and immerse them at 50° C. for 2.5 h. After the treatment, filter and dry to obtain composite slag;

[0064] S2, adding 1 kg of the composite slag in step S1 to 10 L of ethanol aqueous solution (the volume concentration of ethanol is 75%), then adding 170 g of vinyltrimethoxysilane, stirring at 65° C. for 4 h, filtering, washing and drying after the treatment to obtain a composite slag containing double bonds;

[0065] S3. Add 1 kg of the double bond-containing composite slag in step S2 into 10 L of xylene, then add 250 g of allyl dimethyldithiocarbamate, 120 g of acrylic acid, and 15 g of dibenzoyl peroxide, and react at 75 °C for 3.5 h. After the reaction is completed, add sodium hydroxide solution to adjust the pH to 7, then filter, wash, and dry to obtain modified composite slag.

[0066] The method for preparing the modified composite fiber comprises the following steps:

[0067] (a) 1 kg of basalt fiber and 1.5 kg of polyester fiber were added into a low-temperature plasma instrument, and plasma treatment was performed under a nitrogen atmosphere with a vacuum degree of 25 Pa and a power of 110 W for 2 min. After the treatment, pretreated composite fibers were obtained;

[0068] (b) Add 1 kg of the pretreated composite fiber in step (a) into 15 L of dimethylformamide, then add 350 g of 7-amino-1,3-naphthalene disulfonic acid, 150 g of glutaraldehyde, and 450 g of triethylamine, and react in a nitrogen atmosphere at 80° C. for 5 h. After the reaction is completed, filter, wash, and dry to obtain the modified composite fiber.

[0069] Example 3

[0070] A method for preparing a composite slag-based concrete admixture comprises the following steps:

[0071] According to the formula, 5 kg of modified composite slag, 1.5 kg of fly ash, 1 kg of kaolin, 1.5 kg of admixture, and 2.5 kg of modified composite fiber were weighed and stirred at 500 r / min for 30 minutes to obtain the composite slag-based concrete admixture.

[0072] Wherein, the admixture is a mixture of glass microspheres, latex powder, coal gangue and aluminum sulfate in a mass ratio of 15:10:12:5;

[0073] The preparation method of the modified composite slag comprises the following steps:

[0074] S1. Add 1 kg of phosphate slag and 0.5 kg of iron slag into a sodium hydroxide solution with a concentration of 40 g / L, and immerse them at 45° C. for 3 h. After the treatment, filter and dry to obtain composite slag;

[0075] S2, adding 1 kg of the composite slag in step S1 to 10 L of ethanol aqueous solution (the volume concentration of ethanol is 70%), then adding 150 g of vinyltrimethoxysilane, stirring at 60° C. for 5 h, filtering, washing and drying after the treatment to obtain a composite slag containing double bonds;

[0076] S3. Add 1 kg of the double bond-containing composite slag in step S2 into 8 L of xylene, then add 200 g of allyl dimethyldithiocarbamate, 100 g of acrylic acid, and 10 g of dibenzoyl peroxide, and react at 70° C. for 4 h. After the reaction is completed, add sodium hydroxide solution to adjust the pH to 7, then filter, wash, and dry to obtain modified composite slag.

[0077] The method for preparing the modified composite fiber comprises the following steps:

[0078] (a) 1 kg of basalt fiber and 1 kg of polyester fiber were added into a low-temperature plasma instrument, and plasma treatment was performed under a nitrogen atmosphere with a vacuum degree of 20 Pa and a power of 100 W for 3 min. After the treatment, a pretreated composite fiber was obtained;

[0079] (b) Add 1 kg of the pretreated composite fiber in step (a) into 15 L of dimethylformamide, then add 300 g of 7-amino-1,3-naphthalene disulfonic acid, 100 g of glutaraldehyde, and 400 g of triethylamine, and react in a nitrogen atmosphere at 75° C. for 7 h. After the reaction is completed, filter, wash, and dry to obtain the modified composite fiber.

[0080] Example 4

[0081] A method for preparing a composite slag-based concrete admixture comprises the following steps:

[0082] According to the formula, 7 kg of modified composite slag, 2.5 kg of fly ash, 1.5 kg of kaolin, 1 kg of admixture, and 1.5 kg of modified composite fiber were weighed and stirred at 800 r / min for 20 min to obtain the composite slag-based concrete admixture.

[0083] Wherein, the admixture is a mixture of glass beads, latex powder, coal gangue and aluminum sulfate in a mass ratio of 25:15:8:9;

[0084] The preparation method of the modified composite slag comprises the following steps:

[0085] S1. Add 1 kg of phosphate slag and 1 kg of iron slag into a sodium hydroxide solution with a concentration of 80 g / L, and immerse them at 55° C. for 2 h. After the treatment, filter and dry to obtain composite slag;

[0086] S2, adding 1 kg of the composite slag in step S1 to 10 L of ethanol aqueous solution (the volume concentration of ethanol is 80%), then adding 200 g of vinyltrimethoxysilane, stirring at 70° C. for 3 h, filtering, washing and drying after the treatment to obtain a composite slag containing double bonds;

[0087] S3. Add 1 kg of the double bond-containing composite slag in step S2 into 12 L of xylene, and then add 300 g of allyl dimethyldithiocarbamate, 150 g of acrylic acid, and 20 g of dibenzoyl peroxide. React at 80° C. for 3 h. After the reaction is completed, add sodium hydroxide solution to adjust the pH to 7, then filter, wash, and dry to obtain modified composite slag.

[0088] The method for preparing the modified composite fiber comprises the following steps:

[0089] (a) 1 kg of basalt fiber and 2 kg of polyester fiber were added into a low-temperature plasma instrument, and plasma treatment was performed under a nitrogen atmosphere with a vacuum degree of 30 Pa and a power of 130 W for 1 min. After the treatment, pretreated composite fibers were obtained;

[0090] (b) 1 kg of the pretreated composite fiber in step (a) is added to 15 L of dimethylformamide, followed by the addition of 400 g of 7-amino-1,3-naphthalene disulfonic acid, 200 g of glutaraldehyde, and 500 g of triethylamine, and the reaction is carried out in a nitrogen atmosphere at 85° C. for 4 h. After the reaction is completed, the modified composite fiber is filtered, washed, and dried to obtain the modified composite fiber.

[0091] Comparative Example 1

[0092] A method for preparing a composite slag-based concrete admixture comprises the following steps:

[0093] According to the formula, 6 kg of composite slag, 2 kg of fly ash, 1.3 kg of kaolin, 1.2 kg of admixture, and 2 kg of modified composite fiber were weighed and stirred at 700 r / min for 25 minutes to obtain the composite slag-based concrete admixture.

[0094] Wherein, the admixture is a mixture of glass microspheres, latex powder, coal gangue and aluminum sulfate in a mass ratio of 20:13:10:7;

[0095] The preparation method of the composite slag comprises the following steps:

[0096] 1 kg of phosphate slag and 0.8 kg of iron slag were added into a sodium hydroxide solution with a concentration of 60 g / L, and immersed at 50°C for 2.5 hours. After the treatment, the mixture was filtered and dried to obtain composite slag.

[0097] The method for preparing the modified composite fiber comprises the following steps:

[0098] (a) 1 kg of basalt fiber and 1.5 kg of polyester fiber were added into a low-temperature plasma instrument, and plasma treatment was performed under a nitrogen atmosphere with a vacuum degree of 25 Pa and a power of 120 W for 2 min. After the treatment, pretreated composite fibers were obtained;

[0099] (b) Add 1 kg of the pretreated composite fiber in step (a) into 15 L of dimethylformamide, and then add 350 g of 7-amino-1,3-naphthalene disulfonic acid, 150 g of glutaraldehyde, and 450 g of triethylamine, and react in a nitrogen atmosphere at 80° C. for 6 hours. After the reaction is completed, filter, wash, and dry to obtain the modified composite fiber.

[0100] Comparative Example 2

[0101] A method for preparing a composite slag-based concrete admixture comprises the following steps:

[0102] According to the formula, 6 kg of modified composite slag, 2 kg of fly ash, 1.3 kg of kaolin, 1.2 kg of admixture, and 2 kg of composite fiber were weighed and stirred at 700 r / min for 25 min to obtain the composite slag-based concrete admixture.

[0103] Wherein, the admixture is a mixture of glass microspheres, latex powder, coal gangue and aluminum sulfate in a mass ratio of 20:13:10:7;

[0104] The preparation method of the modified composite slag comprises the following steps:

[0105] S1. Add 1 kg of phosphate slag and 0.8 kg of iron slag into a sodium hydroxide solution with a concentration of 60 g / L, and immerse them at 50° C. for 2.5 h. After the treatment, filter and dry to obtain composite slag;

[0106] S2, adding 1 kg of the composite slag in step S1 to 10 L of ethanol aqueous solution (the volume concentration of ethanol is 75%), then adding 180 g of vinyltrimethoxysilane, stirring at 65° C. for 4 h, filtering, washing and drying after the treatment to obtain a composite slag containing double bonds;

[0107] S3. Add 1 kg of the double bond-containing composite slag in step S2 into 10 L of xylene, then add 250 g of allyl dimethyldithiocarbamate, 130 g of acrylic acid, and 15 g of dibenzoyl peroxide, and react at 75 °C for 3.5 h. After the reaction is completed, add sodium hydroxide solution to adjust the pH to 7, then filter, wash, and dry to obtain modified composite slag.

[0108] The method for preparing the composite fiber comprises the following steps:

[0109] 1 kg of basalt fiber and 1.5 kg of polyester fiber were added into a low-temperature plasma instrument. Plasma treatment was performed under a nitrogen atmosphere with a vacuum degree of 25 Pa and a power of 120 W. The treatment time was 2 min. Composite fibers were obtained after the treatment.

[0110] Comparative Example 3

[0111] A method for preparing a composite slag-based concrete admixture comprises the following steps:

[0112] According to the formula, 6 kg of composite slag, 2 kg of fly ash, 1.3 kg of kaolin, 1.2 kg of admixture, and 2 kg of composite fiber were weighed and stirred at 700 r / min for 25 min to obtain the composite slag-based concrete admixture.

[0113] Wherein, the admixture is a mixture of glass microspheres, latex powder, coal gangue and aluminum sulfate in a mass ratio of 20:13:10:7;

[0114] The preparation method of the composite slag comprises the following steps:

[0115] 1 kg of phosphate slag and 0.8 kg of iron slag were added into a sodium hydroxide solution with a concentration of 60 g / L, and immersed at 50°C for 2.5 hours. After the treatment, the mixture was filtered and dried to obtain composite slag.

[0116] The method for preparing the composite fiber comprises the following steps:

[0117] 1 kg of basalt fiber and 1.5 kg of polyester fiber were added into a low-temperature plasma instrument. Plasma treatment was performed under a nitrogen atmosphere with a vacuum degree of 25 Pa and a power of 120 W. The treatment time was 2 min. Composite fibers were obtained after the treatment.

[0118] The admixtures prepared in Examples 1-4 and Comparative Examples 1-3 were applied to concrete. The cement used in the test was P.II 42.5 grade cement. The admixtures were the composite slag-based concrete admixtures prepared in Examples 1-4 and Comparative Examples 1-3. The coarse aggregate was natural crushed stone, which was 5-16 mm granite crushed stone with an apparent density of 2750 kg / m 3 ; Fine aggregate: machine-made sand, fineness modulus 2.4, apparent density 2758kg / m 3 ; The water reducing agent is polycarboxylic acid high-efficiency water reducing agent, and the water reducing rate is 30%; the water is tap water. The concrete ingredients are as shown in Table 2:

[0119] Table 2 Concrete mix ratio used in the test (%)

[0120] cement Admixture Coarse aggregate fine aggregate Water reducing agent water 11.5 4 41.2 36.4 0.7 6.2

[0121] The concrete prepared with the admixtures obtained in Examples 1-4 and Comparative Examples 1-3 was subjected to performance tests, and the compressive strength and flexural strength were determined with reference to GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete"; the chloride ion diffusion coefficient and crack resistance were determined with reference to GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", and the specific data are shown in Table 3.

[0122] Table 3

[0123]

[0124] It can be seen from Table 3 above that the composite slag-based concrete admixture prepared by the present invention, when used in concrete, can improve the overall mechanical properties of concrete, and also has excellent crack resistance and salt erosion resistance, and has good application prospects.

[0125] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A composite slag-based concrete admixture, characterized in that: By weight, it includes the following raw materials: 50-70 parts of modified composite slag, 15-25 parts of fly ash, 10-15 parts of kaolin, 10-15 parts of admixture, 15-25 parts of modified composite fiber; The admixture is a mixture of glass microspheres, latex powder, coal gangue and aluminum sulfate in a mass ratio of 15-25:10-15:8-12:5-9.

2. The composite slag-based concrete admixture according to claim 1, characterized in that: By weight, it includes the following raw materials: 50-60 parts of modified composite slag, 20-25 parts of fly ash, 10-15 parts of kaolin, 10-15 parts of admixture, and 20-25 parts of modified composite fiber.

3. The composite slag-based concrete admixture according to claim 1, characterized in that: The preparation method of the modified composite slag comprises the following steps: S1, adding phosphate slag and iron slag into sodium hydroxide solution for impregnation treatment, filtering and drying after the treatment to obtain composite slag; S2, adding the composite slag in step S1 to an ethanol aqueous solution, then adding vinyltrimethoxysilane, stirring, filtering, washing, and drying after the treatment to obtain a composite slag containing double bonds; S3, adding the double bond-containing composite slag in step S2 into xylene, and then adding allyl dimethyldithiocarbamate, acrylic acid, and dibenzoyl peroxide to carry out a constant temperature reaction, and after the reaction is completed, adding a solution to adjust the pH to 7, followed by filtering, washing, and drying to obtain a modified composite slag.

4. The composite slag-based concrete admixture according to claim 3, characterized in that: In step S1, the mass ratio of the phosphate slag to the iron slag is 10:5-10, the concentration of the sodium hydroxide is 40-80 g / L, the temperature of the immersion treatment is 45-55° C., and the time is 2-3 h.

5. The composite slag-based concrete admixture according to claim 3, characterized in that: The volume concentration of ethanol in the ethanol aqueous solution in step S2 is 70-80%, the mass ratio of the composite slag to vinyltrimethoxysilane is 100:15-20, the temperature of the stirring treatment is 60-70° C., and the time is 3-5 hours.

6. The composite slag-based concrete admixture according to claim 3, characterized in that: In step S3, the mass ratio of the pretreated composite slag, xylene, allyl dimethyldithiocarbamate, acrylic acid, and dibenzoyl peroxide is 100:800-1200:20-30:10-15:1-2, and the isothermal reaction temperature is 70-80° C. and the reaction time is 3-4 hours.

7. The composite slag-based concrete admixture according to claim 1, characterized in that: The method for preparing the modified composite fiber comprises the following steps: (a) adding basalt fiber and polyester fiber into a low-temperature plasma apparatus for plasma treatment, and obtaining pretreated composite fiber after the treatment; (b) adding the pretreated composite fiber in step (a) into dimethylformamide, and then adding 7-amino-1,3-naphthalene disulfonic acid, glutaraldehyde, and triethylamine, heating to react under a nitrogen atmosphere, and filtering, washing, and drying after the reaction is completed to obtain the modified composite fiber.

8. The composite slag-based concrete admixture according to claim 7, characterized in that: In step (a), the mass ratio of the basalt fiber to the polyester fiber is 1:1-2, and the plasma treatment process is as follows: under a nitrogen atmosphere, the vacuum degree in the vacuum chamber of the plasma instrument is 20-30 Pa, the treatment time is 1-3 min, and the treatment power is 100-130 W.

9. The composite slag-based concrete admixture according to claim 7, characterized in that: In step (b), the mass ratio of the pretreated composite fiber, 7-amino-1,3-naphthalene disulfonic acid, glutaraldehyde and triethylamine is 100:30-40:10-20:40-50; the temperature of the heating reaction is 75-85° C. and the time is 4-7 hours.

10. A method for preparing the composite slag-based concrete admixture according to any one of claims 1 to 9, characterized in that: The following steps are involved: The modified composite slag, fly ash, kaolin, admixture and modified composite fiber are weighed in parts by weight, and stirred at 500-800 r / min for 20-30 min to obtain the composite slag-based concrete admixture.

Citation Information

Patent Citations

  • Titanium slag powder-phosphorus slag powder composite admixture, and preparation method and application method thereof

    CN110240434A

  • Method for producing composite mineral admixture from ferromanganese slag

    CN113233830A